The Difficult Case of Persuading Women: Experimental Evidence from Childcare - Vincenzo Galasso; Paola Profeta; Chiara D. Pronzato; Francesco C. Billari (Institute for the Study of Labor (IZA), 2013)
Gender stereotypes are well established also among women. Yet, a recent literature suggests that learning from other women experience about the effects of maternal employment on children outcomes may increase female labor force participation. To further explore this channel, we design a randomized survey experiment, in which 1500 Italian women aged 20 to 40 are exposed to two informational treatments on the positive consequences of formal childcare on children future educational attainments. Surprisingly, we find that women reduce their intended labor supply. However, this result hides strong heterogenous effects: high educated non-mothers are persuaded by the informational treatments to increase their intended use of formal child care (and to pay more); whereas low educated non-mothers to reduce their intended labor supply. These findings are consistent with women responding to monetary incentive and/or having different preferences for maternal care. These heterogenous responses across women send a warning signal about the true effectiveness in terms of take up rates of often advocated public policies regarding formal child care.
Keywords: J2; J16; J13; J18; Z1; C99; 330; gender culture; female labour supply; education; Kinderbetreuung; Weibliche Arbeitskräfte; Arbeitsangebot; Mütter; Stereotyp; Soziale Gruppe; Italien